Navigating the challenges of TEFL in resource-limited elementary school: insights from Yogyakarta - Suryanto, Jati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Teaching English as a Foreign Language (TEFL) in elementary schools, particularly in resource-limited settings, presents significant challenges. In Yogyakarta, Indonesia, these challenges are intensified in a public school, where limited resources, such as teaching materials, technology, and professional development opportunities, hinder the ability of teachers to deliver effective language instruction. Despite these constraints, English remains a crucial part of the education system in Indonesia, with increasing recognition of its importance for academic, professional, and social advancement. This study aims to explore the specific challenges faced by teachers in a public elementary school in Yogyakarta, and the strategies they employ to overcome these challenges in teaching English to young learners. A qualitative research design was employed, with data collected through interviews with three experienced teachers from the early stages in the school. The study identifies key challenges, including students’ difficulties with pronunciation, short attention spans, bilingualism, and the quick forgetting of lessons. It also highlights strategies that teachers use to address these issues, such as incorporating fun songs and videos, using games, and employing interactive methods to engage students. The findings underscore the importance of creative, low-cost strategies in overcoming resource limitations and fostering an engaging and effective learning environment. This research contributes valuable insights into TEFL practices in resource-constrained contexts and offers recommendations for improving English language teaching in similar settings worldwide.